Nanocomposites VI: Nanoscience and Nanotechnology in Advanced Composites - Srivatsan, T. S.; Gupta, Manoj; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume presents novel and innovative contributions in the domain specific to nanocomposites, specifically on aspects both related and relevant to the following: · science at the nanoscale level · innovations and advances in processing · characterization, quantification, and analysis · mechanical property evaluation and rationalization · failure analysis · technological applications at the nanoscale level The collection brings together a range of developments in areas spanning basic science, processing, analysis, characterization, mechanical property evaluation, and failure analysis rationalization of composite materials. .
Keywords: Nanotechnology; Microtechnology; Microelectromechanical systems; Ceramic materials; Materials -- Analysis; Nanotechnology; Microsystems and MEMS; Ceramics; Characterization and Analytical Technique